Identification des paramètres électriques d'un panneau photovoltaïques en utilisant les algorithmes génétiques. - مصطفاوي, عائشة (university of Eloued جامعة الوادي, 2019)
the performance of a photovoltaic module can be described by the I-V characteristic that is affected by the different electrical parameters. In this work, an evolutionary technique based on genetic algorithms was used to extract the electrical parameters of a photovoltaic module. Based on the analytical model of the current-voltage of a solar cell with a single diode, the latter has been solved and the results are compared to experimental ones where a good agreement is found. In addition, the technique based on the genetic algorithmic approach is a very promising way in determining the electrical parameters of a photovoltaic module based on experimental measurements of their I (V) characteristics. يمكن وصف أداء الوحدة الكهروضوئية بواسطة الخاصية I-V التي تتأثر بالمعلمات الكهربائية المختلفة. في هذا العمل ، تم استخدام تقنية تطورية مبنية على خوارزميات جينية لاستخلاص المعلمات الكهربائية لوحدة ضوئية. واستناداً إلى النموذج التحليلي للجهد الحالي للخلية الشمسية ذات الصمام الثنائي الواحد ، تم حل هذه الأخيرة وتمت مقارنة النتائج بالنتائج التجريبية حيث تم التوصل إلى اتفاق جيد. بالإضافة إلى ذلك ، فإن التقنية القائمة على المنهج الوراثي الخوارزمي هي طريقة واعدة جدًا في تحديد المعلمات الكهربائية لوحدة ضوئية مبنية على قياسات تجريبية لخصائصها I (V).
مذكرة ماستر تخصص في انظمة الاتصالات
Keywords: photovoltaic, solar cells, electrical parameters; الكهروضوئية، الخلايا الشمسية، المعلمات الكهربائية